FILM ANIMASI 3D JURNALIS SINDO - Yenni Mariana (Besaung : Jurnal Seni Desain dan Budaya, 2017)
3-Dimension Sindo's Journalist Animation Movie tells about a journalist's deception. 3 Dimensional animated film using Low Poly technique. Low Poly is a computer graphics that has a small number of polygons. This modeling technique reduces the detail of a 3-dimensional model with the purpose of geometry efficiency that can lighten the system's workload while designing and when rendering. Software used in the making of this film is Blender 3D, Adobe Illustrator, Adobe PhotoShop, Adobe. Premiere, Corel Draw and Format Factory.Use visual concepts derived from verbal language that is processed into visual language, in concept there are some elements, such as creativity, aesthetics, efficiency, communicative, and others to be accepted by the target audience. Visual object processing requires the composition of design formats, layouts, typography, illustrations, and colors to make the visual messages and messages delivered easily accepted by target audiences. Key words : Animation Movie, 3 Dimension, Low Poly, Sindo